Parameters associated with active caries lesions assessed by two different visual scoring systems on occlusal surfaces of primary molars-a multilevel approach (2010)
The aim of this in vivo study was to evaluate the association between several parameters related to children and to their teeth, and the presence of active carious lesions assessed by two different visual indices on occlusal surfaces of primary molars. Occlusal surfaces of 757 primary molars in 139 children (3–12 years old) were classified as sound, or having inactive or active carious lesions using the Nyvad criteria (NY) and the International Caries Detection and Assessment System (ICDAS‐II) and a supplemental lesion activity assessment system (ICDAS‐LAA). Several parameters related to the tooth and to the child were recorded. Associations between these parameters and the presence of active carious lesions on occlusal surfaces were evaluated using logistic multilevel analysis. Second primary molar teeth and children with high caries experience were more frequently with active occlusal carious lesions compared to sound and inactive occlusal carious lesions classified by both visual scoring systems. Teeth with a mature dental plaque on the occlusal surface and younger children had more active caries than inactive occlusal carious lesions (excluding sound teeth in the analysis). A previous visit to a dentist was related to a lower frequency of active occlusal carious lesions classified by NY only, and upper primary molars presented with higher numbers of active occlusal carious lesions classified by ICDAS‐LAA. Presence of mature dental plaque and tooth type are tooth‐related variables associated with active carious lesions on occlusal surfaces of primary teeth, as well as anterior caries experience and age are variables related to the child.